2010
DOI: 10.1007/s11894-010-0115-2
|View full text |Cite
|
Sign up to set email alerts
|

Perianal Infections: A Primer for Nonsurgeons

Abstract: The topic of perianal infections covers a broad range of illnesses that can be difficult to differentiate from each other. As a result, patients may suffer from unnecessary examinations and ineffective or delayed therapeutic interventions. This article reviews common and unusual infectious pathology and inflammatory or malignant conditions that should be considered in the differential diagnosis. Presentations of infectious pathology specific to HIV are discussed. New treatment strategies, where available, are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…genital herpes, syphilis, gonorrhea and genital warts. Itching occurs most frequently in the course of HPV infection (13). In our study, the diagnosis was confirmed in one patient with small papillous eruptions around the anus.…”
Section: Discussionsupporting
confidence: 75%
“…genital herpes, syphilis, gonorrhea and genital warts. Itching occurs most frequently in the course of HPV infection (13). In our study, the diagnosis was confirmed in one patient with small papillous eruptions around the anus.…”
Section: Discussionsupporting
confidence: 75%